Long-term effects of a dyadic planning intervention with couples motivated to increase physical activity. (July 2020) - Keller, Jan; Hohl, Diana Hilda; Hosoya, Georg; Heuse, Silke; Scholz, Urte; Luszczynska, Aleksandra; Knoll, Nina
Abstract: Objective: In dyadic planning a target person and a planning partner create plans for when, where, and how the target person will change a health-relevant behavior. Across 52 weeks, direct and indirect effects of a dyadic-planning intervention on moderate-to-vigorous physical activity (MVPA) and physical fitness in target persons and their partners were investigated in a randomized controlled trial. Relationship quality was explored as a moderator. Methods: N  = 338 couples (target persons randomized) were randomly assigned to a dyadic-planning- (DPC), an individual-planning- (IPC), or a no-planning dyadic-control condition (CC). MVPA was objectively assessed four times across 52 weeks using accelerometry. Physical fitness and proposed mediators (individual action control, received behavior-specific support and control) were repeatedly assessed. Relationship quality was measured at baseline. Latent growth curve-, multi-level-, and manifest mediation models were fit. Results: Across 52 weeks, MVPA of IPC and CC target persons increased. MVPA of DPC target persons remained stable, but those who reported high relationship quality increased their MVPA over time. DPC partners showed steeper increases in physical fitness when compared to IPC partners, but not CC partners. DPC partners' increases in physical fitness were mediated by received support from target persons. Conclusions: The dyadic planning intervention showed non-beneficial effects for target persons' MVPA, but beneficial effects on their partners' fitness. These findings resemble evidence from the social support literature indicating more benefits for support providers than for recipients. Trial registration: ClinicalTrials.gov identifier: NCT01963494. Highlights: Recipients of a dyadic planning intervention did not increase in physical activity. Only dyadic planning target persons with high relationship quality benefited. Partners who helped forming dyadic plans improved in physical fitness over one year. Further evidence on more health benefits for support providers than for recipients.